Analisis Kemampuan Berpikir Kritis Matematis Siswa ditinjau dari Gender - Liunokas, Dewani S.; Gella, Netty J. M.; Daniel, Farida (Universitas Muria Kudus, 2023)
Mathematical critical thinking is the ability to solve problems using knowledge, reasoning, and mathematical proof. This research aims to test students' mathematically necessary thinking abilities based on gender. The subjects of this research were students of class X TKJ SMKN 2 Soe. This research method is descriptive-qualitative, where data collection uses observation techniques, tests in the form of story questions, and semi-structured interviews. Data analysis in this research uses the Miles and Huberman technique in data reduction, data presentation, and concluding/verification. Data validity testing uses technical triangulation. The results of the research show that there is no significant difference in students' mathematical critical thinking abilities based on gender. Most male and female students can fulfil all indicators of mathematical critical thinking, namely providing simple explanations, building basic skills, drawing conclusions and further explanations, and determining problem-solving strategies and tactics. Female students are more detailed in the problem-solving process based on stages, while male students are less detailed.